Microwave-absorption characteristics of polyaniline-coated multi-walled carbon nanotube composites. (21st April 2021) - Haritha, T.; Ramji, K.; Subrahmanyam, Ch; Krushnamurthy, K.; Nagasree, P. S.
ABSTRACT: In this study, the microwave-absorption characteristics of multi-layered radar-absorbing structures (RASs) were investigated. Electrical-grade glass (e-glass)/epoxy composites containing modified multi-walled carbon nanotubes (MWCNTs) were fabricated. The poly aniline (PANI) coated MWCNTs was obtained by in-situ polymerisation of aniline in the presence of MWCNTs. The PANI-coated MWCNTs (PCNTs) were then used as reinforcements in the polymer matrix, and their morphologies, microstructures, thermal stabilities, and microwave-absorbing properties were investigated. The complex permittivity and permeability of the composites were measured and found to have increased with increasing filler concentration. Microwave absorbing properties were analysed via waveguide measurement. The three-layered RASs reinforced with PCNTs having a thickness of 4 mm exhibited a RL of –5 dB over the entire X-band and a reflection peak of –24.53 dB at 10.0 GHz. Hence, the epoxy/PCNTs composites are suitable for use in microwave-absorption applications.